The Relationship Between Affect in Dreams and Emotional Memory Consolidation - Du Plessis, Li?tte (Department of Psychology, 2024)
Research in the field of cognitive neuroscience has focused on the role of sleep in various neurocognitive processes such as memory consolidation, however, an area that has not been fully researched is the role of dreaming in these memory processes. This study aimed to determine the relationship between affect experienced in dreams and emotional memory consolidation. Considering that REM dreams are laden with emotion and that emotion enhances memory, one possibility is that dreaming affect could also play a role in emotional memory consolidation. The hypothesis was that the greater the intensity of affect in a dream, the greater the memory retention will be for emotional information, but not neutral information. 126 healthy participants, aged 18 – 50, were recruited. On the night of the study, the participant viewed a series of pictures from the SA-APS in an online environment. Afterwards, they verbally recalled as many pictures as possible. The following morning, they were asked to recall any dreams and rate the emotional intensity of their dreams. Participants then again verbally recalled all the pictures that they could remember from the previous night. Contrary to the prediction, affect intensity, regardless of valence, did not predict memory consolidation of valenced information. The findings rather showed a general effect of dream affect intensity on overall memory retention. Furthermore, a specific emotion, fear, seemed to drive this general consolidation effect. The secondary analysis revealed that an increase in negative affect in dreams predicted better memory retention of negative information. Increased negative affect may create a need for increased mental processing and, in turn, support better memory consolidation. These findings have implications for psychiatric disorders, such as major depression, which is characterised by negative affect and increased memory sensitivity for negative stimuli. Keywords: affect, dreams, emotional memory consolidation, REM sleep